2022
DOI: 10.1785/0320220007
|View full text |Cite
|
Sign up to set email alerts
|

The Far Side of Mars: Two Distant Marsquakes Detected by InSight

Abstract: For over three Earth years the Marsquake Service has been analyzing the data sent back from the Seismic Experiment for Interior Structure—the seismometer placed on the surface of Mars by NASA’s InSight lander. Although by October 2021, the Mars seismic catalog included 951 events, until recently all these events have been assessed as lying within a radius of 100° of InSight. Here we report two distant events that occurred within days of each other, located on the far side of Mars, giving us our first glimpse i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
62
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(64 citation statements)
references
References 37 publications
2
62
0
Order By: Relevance
“…• While first layered models of the crust and mantle, including the radius of the core were obtained by InSight using a single station only (Durán et al 2022;Khan, Ceylan, et al 2021;Knapmeyer-Endrun et al 2021; Tharsis (Horleston et al 2022) suggests that much more small seismicity could be present there, unobservable from InSight's location. At the same time, Plesa et al (2021) showed that geodynamical models predict significant lateral variations in seismic wave speed, potentially higher than on Earth.…”
Section: Potential Scientific Goalsmentioning
confidence: 99%
“…• While first layered models of the crust and mantle, including the radius of the core were obtained by InSight using a single station only (Durán et al 2022;Khan, Ceylan, et al 2021;Knapmeyer-Endrun et al 2021; Tharsis (Horleston et al 2022) suggests that much more small seismicity could be present there, unobservable from InSight's location. At the same time, Plesa et al (2021) showed that geodynamical models predict significant lateral variations in seismic wave speed, potentially higher than on Earth.…”
Section: Potential Scientific Goalsmentioning
confidence: 99%
“…
The most distant marsquake, S0976a, recorded so far by the InSight seismometer occurred at an epicentral distance of 146.3 ± 6.9 o (Horleston et al, 2022), close to the western end of Valles Marineris.We have identi ed both SS and PP precursors, i.e., underside re ections off the crust-mantle (or intracrustal) discontinuity between the marsquake and the instrument, on the seismograms, which directly constrain the crustal structure away (4000 km) from the InSight landing site. Inversion results show that the Martian crust at the bounce point between the lander and the event is characterized by an interface at 20 ± 5 km depth, similar to that seen beneath the InSight landing site (Knapmeyer-Endrun et al, 2021).However, a likely distinct feature at the bounce point compared to the lander site is the absence of a shallow layer (at 8 ± 2 km, with low seismic wave speed, Knapmeyer-Endrun et al, 2021), indicating that this layer is either local structure beneath the lander or related to the type of geologic unit or that has been obscured at the bounce point by later processes.
…”
mentioning
confidence: 95%
“…The most distant marsquake, S0976a, recorded so far by the InSight seismometer occurred at an epicentral distance of 146.3 ± 6.9 o (Horleston et al, 2022), close to the western end of Valles Marineris.…”
mentioning
confidence: 95%
See 2 more Smart Citations